2020
DOI: 10.1007/s12254-020-00577-1
|View full text |Cite
|
Sign up to set email alerts
|

AML—is it time to drive a CAR(-T)?

Abstract: The treatment options for newly diagnosed and relapsed/refractory acute myeloid leukemia (AML) have substantially improved over the last 5 years. However, even though novel targeted agents (e.g. venetoclax, IDH1/2 and novel FLT-3 inhibitors; cytosolic isocitrate dehydrogenase 1/2 and fms-like tyrosine kinase 3 inhibitor) and improved chemotherapeutics (e.g. CPX-351; liposomale Daunorubicin/ Cytarabine) are entering clinics, physicians are still confronted with high relapse and treatment failure rates. Thus, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…One approach to enforce tumor recognition by T cells is by making use of chimeric antigen receptors, or CARs 134,138,139 . A CAR is constructed from the variable region of a high affinity tumor antigen‐specific antibody targeting a tumor antigen, that is CD19 or CD33, 136,140 coupled to the signalling domain of CD3 and the signalling domain of one or more costimulatory molecules, for example CD28. As a result, T cells can be equipped with a CAR which serves as a complete signalling module for T cell activation 138 …”
Section: Employing Tlr Signalling In T Cell‐based Therapeutic Approachesmentioning
confidence: 99%
“…One approach to enforce tumor recognition by T cells is by making use of chimeric antigen receptors, or CARs 134,138,139 . A CAR is constructed from the variable region of a high affinity tumor antigen‐specific antibody targeting a tumor antigen, that is CD19 or CD33, 136,140 coupled to the signalling domain of CD3 and the signalling domain of one or more costimulatory molecules, for example CD28. As a result, T cells can be equipped with a CAR which serves as a complete signalling module for T cell activation 138 …”
Section: Employing Tlr Signalling In T Cell‐based Therapeutic Approachesmentioning
confidence: 99%
“…It is reported that FLT3 inhibitors have demonstrated promising results in clinical settings with minimal side effects [ 17 , 18 ]. The standard treatment option includes chemotherapy and a bone marrow (BM) transplant [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Rudzki et al focused on the importance of CAR-T cell therapy in r/r AML (acute myeloid leukemia), illustrating current results and providing an overview of the most promising cellular strategies to handle r/r AML with CAR-T cell-or TCRapproaches [4].…”
mentioning
confidence: 99%